ANZACS on the Western Front the Australian War Memorial battlefield guide - Pedersen, Peter A. 1952-; Roberts, Chris 1945- (John Wiley & Sons Australia, 2011)
"ANZACS on the Western Front : the Australian War Memorial battlefield guide" is the definitive guide to the Western Front battlefields. Meticulously researched and written by the Head of Research at the Australian War Memorial, Dr Peter Pedersen, this landmark publication guides readers chronologically through the battles in which Australians and New Zealanders fought on the Western Front from 1916-1918. Lavishly illustrated in vibrant colour, with fascinating images from the Australian War Memorial archive as well as new panoramic location shots to provide an in situ perspective for the reader, each chapter covers the important tactical milestones passed along the way and explains how the Australian Imperial Force and the New Zealand Expeditionary Force evolved to meet the war's changing demands